THE REINTERPRETATION OF HORA IN ITINERE POST-LABOR REFORM: THE THEORY OF PRODUCTIVE DEVIATION OF TIME AS AN INSTRUMENT FOR THE PROTECTION OF WORKER'S DIGNITY (Reflection and Critique Law Magazine, 2026)
The labor reform enacted by Law No. 13,467/2017 brought practical consequences for all labor-related relationships within the Brazilian legal framework, altering concepts and structures already established in doctrine and jurisprudence on various topics, particularly regarding the worker's right to "hora in itinere" (commuting time). This text aims to analyze the significant changes in labor legislation with the elimination of the employee's right to "hora in itinere," both in doctrine and jurisprudence, especially the possibility or not of the employer's obligation to bear the cost of commuting time, even without legal provision in Law 13,467/2017. To achieve this, jurisprudential research and doctrinal framework will be utilized, applying the theory of the consumer's productive deviation or the autonomy of temporal damage in civil law relations, as well as providing a momentary critique of the legislative change with the potential for employer liability in light of this theory.